Dosis Kombinasi Bioarang Sekam Padi dan Berbagai Amandemen di Tanah Sulfat Masam - Agusalim Masulili; Sutikarini Sutikarini; Rini Suryani (Jurnal Ilmu Pertanian Indonesia, 2023)
This study aims to determine the effect of various doses of rice husk biochar combined with organic amendments of cow manure and inorganic amendments of recommended fertilizer packages (urea, TSP, and KCl) on acid-sulfate soils. Over four months, the study was conducted in the Experimental Land of the Center for the Assessment of Agricultural Technology (BPTP) Pal IX, West Kalimantan Province. The study employed a randomized block design, with treatments including control soil, rice husk biochar 6 t ha-1, rice husk biochar 8 t ha-1, rice husk biochar 10 t ha-1, rice husk biochar 12 t ha-1, package of recommended inorganic fertilizer, package of recommended inorganic fertilizer + rice husk biochar 10 t ha-1, manure 10 t ha-1, and 10 t ha-1 + rice husk biochar 10 t ha-1. The findings revealed that single rice husk biochar amendments and their combination with inorganic and organic amendments had varying effects on the improvement of several physical properties of acid sulfate soils (density, total pore, moisture content, and penetration resistance). The amendment of a single biochar with a dose of 12 t ha-1 resulted in the lowest bulk density of acid sulfate soil, which decreased by 16% compared to the control soil. At a dose of 12 t ha-1, rice husk biochar produced the highest porosity and soil moisture content, 55% and 17%, respectively. The soil strength, as measured by the lowest penetration resistance, decreased by 30% in the treatment of manure 10 t ha-1 + biochar 10 t ha-1 (350 N cm-2) compared to the control soil. Keywords: biochar rice husk, soil amendment, soil properties of acid sulphate